2013
DOI: 10.1088/0957-4484/24/48/484005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of morphology and polymer:nanoparticle ratio on device performance of hybrid solar cells—an approach in experiment and simulation

Abstract: We present a thorough study on the various impacts of polymer:nanoparticle ratios on morphology, charge generation and device performance in hybrid solar cells, comprising active layers consisting of a conjugated polymer and in situ prepared copper indium sulfide (CIS) nanoparticles. We conducted morphological studies through transmission electron microscopy and transient absorption measurements to study charge generation in absorber layers with polymer:nanoparticle weight ratios ranging from 1:3 to 1:15. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…8 Therefore, CuInS 2 nanocrystals nd applications in numerous elds 9 including bioimaging, 10 photocatalysis, 11 light emitting diodes 12 and, in particular, solar energy conversion devices like semiconductor sensitized mesoscopic solar cells, [13][14][15] quantum dot solar cells, 16 as well as hybrid bulk heterojunction polymer/nanoparticle solar cells. [17][18][19] For the synthesis of copper indium sulde nanoparticles, numerous routes are reported, whereby a majority of them can be referred to as colloidal synthesis routes (heat up and hot injection syntheses), solvothermal routes as well as in situ syntheses in a polymeric matrix material. 9,[20][21][22] Almost all of these routes involve heat treatment at a certain stage in the synthetic procedure.…”
Section: Introductionmentioning
confidence: 99%
“…8 Therefore, CuInS 2 nanocrystals nd applications in numerous elds 9 including bioimaging, 10 photocatalysis, 11 light emitting diodes 12 and, in particular, solar energy conversion devices like semiconductor sensitized mesoscopic solar cells, [13][14][15] quantum dot solar cells, 16 as well as hybrid bulk heterojunction polymer/nanoparticle solar cells. [17][18][19] For the synthesis of copper indium sulde nanoparticles, numerous routes are reported, whereby a majority of them can be referred to as colloidal synthesis routes (heat up and hot injection syntheses), solvothermal routes as well as in situ syntheses in a polymeric matrix material. 9,[20][21][22] Almost all of these routes involve heat treatment at a certain stage in the synthetic procedure.…”
Section: Introductionmentioning
confidence: 99%
“…There are few examples of CuInS 2 or Cu(In,Ga)Se 2 solar cells being deposited from precursors using common organic solvents1617181920. Until now, these works have utilized metal xanthate precursors which must be prepared using carbon disulfide, which poses health and reactivity problems like hydrazine.…”
mentioning
confidence: 99%
“…As the PL quenching experiments revealed that with a PPD–BDT:CIS ratio of 1:12 no further quenching of the PL can be obtained, we chose a weight ratio of 1:9 for the preparation of the hybrid solar cells, a weight ratio which already turned out to lead to good results for other polymers [13, 14]. The solar cells were prepared in the architecture glass/ITO/PEDOT:PSS/PPD–BDT—CIS/Ag and the IV curves of a typical PPD–BDT/CIS solar cell are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%